2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26063
|View full text |Cite
|
Sign up to set email alerts
|

Redesigning Computer Engineering Gateway Courses Using a Novel Remediation Hierarchy

Abstract: Focusing on the quality of education, skills, and employability of our graduates in computingrelated fields, this work proposes a cost-effective approach to achieve these goals. The Evaluation and Proficiency Infrastructure, Curricula, and Services (EPICS) extends successful methods in other units on campus in an innovative way as synergistic combination of faculty, Graduate Teaching Assistants (GTAs), and educational technology using the Canvas Webcourses Learning Management System (LMS) already in use at our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…Computer-based exams have been proposed as a means of mitigating the tension between scale and excellence in assessment in engineering classes (DeMara et al, 2016;Shacham, 1998;Zilles et al, 2015). Such exams allow a broad range of questions (e.g., numeric, graphical, symbolic, programming, and drawing) to be autograded and to provide students with immediate feedback (Carrasquel, 1985;Rytkönen & Myyry, 2014;Shacham, 1998;West, Herman, & Zilles, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Computer-based exams have been proposed as a means of mitigating the tension between scale and excellence in assessment in engineering classes (DeMara et al, 2016;Shacham, 1998;Zilles et al, 2015). Such exams allow a broad range of questions (e.g., numeric, graphical, symbolic, programming, and drawing) to be autograded and to provide students with immediate feedback (Carrasquel, 1985;Rytkönen & Myyry, 2014;Shacham, 1998;West, Herman, & Zilles, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Trends of increasing enrollment, reduction in costs of PCs, and the success of computerized testing in other disciplines have been motivating its recent research in Engineering . For instance, the University of Utah and Brigham Young University (BYU) Testing Centers (TCs) recently provide computerized testing facilities for engineering and science programs using digitized assessments.…”
Section: Selected Related Workmentioning
confidence: 99%
“…On the other hand, skill inventories in a study spanning 25 sections of college physics course showed that participation in asynchronous online CBA varied significantly based on the students’ ranking within the course . Thus to increase engagement and rapid remediation for all students uniformly, the testing assessment center‐based approach developed herein promulgates an integrated testing and tutoring methodology . The designated testing center used by the authors’ college has been successfully adapted to support a broad range of STEM programs .…”
Section: Selected Related Workmentioning
confidence: 99%
See 2 more Smart Citations